O PROJETO DE LE CORBUSIER DE 1929 E O DESENVOLVIMENTO DA CIDADE DO RIO DE JANEIRO - Moreira, Mariana Fernandes (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
One has to analyze and study the project made to the city of Rio de Janeiro by Le Corbusier in 1929 and the visits to Brazil. We considered three main regents factors: economics, politics and society. First covering and analyzing all background to coming of the architect to Brazil. Analyze the visit mainly the contacts of Le Corbusier and as he was entering his moderns ideas and helping to develop the Brazilian modernism in the field of architecture and urbanism. Search view the legacy left Le Corbusier in Brazil, all the influence that he mainly from urban concepts, and how was reverberating over time, taking into account the Letter of Athens and all the repercussions. Also relate to the Charter of Athens with planning and urban design desenvoldido by Lucio Costa and Oscar Niemeyer for the city of Brasilia in 1956, focusing all adopted precepts. Finally, get a brief discurssão on the lessons of modern urbanism of Le Corbusier to the present reflective way, showing how some factors have developed over time.